Physics and Engineering of New Materials - Cat, Do Tran (Springer, 2017)
Under the general title "Physics and Engineering of New Materials" the book covers experimental and theoretical cutting-edge material-physics oriented topics such as new materials, magnetism, nanostructures, surface physics, carbon nanotubes, photonics, biophysics, large-scale simulations, etc.